Rational Design of Chemical Bath Deposition Technique for Successful Preparation of Mn-Doped CdS Nanostructured Thin Films With Controlled Optical Properties - Kharabaneh, Farzaneh Khani; Ghavidel, Elham; Soheyli, Ehsan; Yazici, Ahmet Faruk; Jawhar, Nawzad Nadhim; Mutlugun, Evren; Sahraei, Reza (Elsevier Sci Ltd, 2021)
The introduction of a rational design for depositing internally-doped nanostructured thin films is of great importance for optoelectronics. In this presented work, Mn-doped CdS thin films with high purity in composition were prepared through the chemical bath deposition technique using a nucleation-doping strategy. This work focuses on an improved chemical design to eliminate mostly ignored property of conventionally doped nanoscale thin films. The synthesis strategy was initiated by the initial formation of MnS nuclei in a colloidal depositing solution followed by injection of cadmium precursor to diffuse into the initial nuclei and play the role of host CdS matrix which was the beginning of the deposition process. Upon optimization of the PL-emission, it was revealed that relative intensity of Mn2+-related peak to the excitonic peak has significantly increased (similar to 100 times) in 80 degrees C, pH = 6, and precursor molar ratio of Cd:Mn:EDTA:S equal to 1:3:0.4:5, at deposition time of 300-min. The TRPL measurements further revealed the effective contribution of Mn-related midgap states with long-lived decay curve character, which confirms the success of the designed approach to reach internally doped thin films. It was found that the deposition temperature, amount of Cd/Mn/TA precursors, and deposition time are the most important experimental parameters in the proposed synthesis approach. Due to the versatility, generality, and colloidal advantages of this method, it can be extended to the other structures with various types of dopant agent.
Mutlugun, Evren/0000-0003-3715-5594; Sahraei, Reza/0000-0001-7104-2126; Ghavidel, Elham/0009-0001-6469-692X; Yazici, Ahmet Faruk/0000-0003-2747-7856; Soheyli, Ehsan/0000-0002-1403-7934
Keywords: Thin Films; Mn-Doped Cds; Colloidal Nucleation Doping; Chemical Bath Deposition; Mn-Related Emission